Stabilisasi merkuri pada limbah tambang dengan menggunakan zeolit alam - Budianta, Wawan; Idrus, Arifudin; Kurniawan, Winarto; Prastistho, Widyawanto (Al-Ard: Jurnal Teknik Lingkungan, 2023)
Mercury contamination caused by artisanal gold mining waste would become an environmental problem if there were no remediation actions. This study aimed to investigate the ability of natural zeolite obtained from Gunungkidul Yogyakarta to stabilize mercury in mining waste or tailing. Tailing samples were obtained from three locations on Kulon Progo, Wonogiri, and Banyumas, and the natural zeolite sample was obtained from Gunungkidul, Yogyakarta. The batch experimental study was conducted to test the ability of the effectiveness of natural zeolite in stabilizing mercury in tailing. The result of the study shows that the natural zeolite used in the experimental study can be used to reduce the mercury concentration in tailing. The natural zeolite's ability for stabilization varies and depends on the initial mercury concentration in tailing and the natural zeolite dose.